Financial awareness and business development cognition positively influence the sustainable development of rural family businesses - Xingpeng, Zheng; Tham, Jacquline; Khatibi, Ali (Frontiers in Sociology, 2025)
Family businesses are the primary form of economic organization worldwide. In most countries, family businesses account for 70 to 90% of the annual global gross domestic product (GDP) and 50 to 80% of all jobs. In rural areas of China, the number of family farms engaged in cultivation is estimated to be up to 4 million as of October 2023. Family businesses exhibit unique characteristics compared to non-family businesses, and further research is needed on how to promote their sustainable development. Therefore, we constructed structural equation model (SEM) to explore the role of family business operators’ business development cognition and financial awareness in sustainable development and investigated 507 family business operators of rural cultivation. We used SPSS 25.0, AMOS 24.0 to analyse the data. Research results indicated that the business development cognition (β = 0.327, p < 0.001) and financial awareness of family business operators (β = 0.294, p < 0.001) positively influenced the sustainable development of family businesses. In this process, the abilities of family business operators to run businesses played a moderating role. This study complemented and improved the Upper Echelons Theory (UET), and pointed out that the ability of CEOs alone was not enough to promote the development of rural family firms, and the combination of CEO’s cognition of business development, financial awareness and abilities to run businesses was needed to promote the sustainable development of rural family firms. Then, several implications have been provided for family business operators.